Perhitungan Kebutuhan Tenaga Medis Berdasarkan Workload Indicators of Staffing Need (WISN): Studi Kasus di Rs A, Rs B, Rs C, Rs D - Nasution, Ali Napiah; Nasution, Sri Lestari Ramadhani; Nasution, Sri Wahyuni (Jurnal Keperawatan Muhammadiyah, 2020)
Indicators showing how needs of steam in health facilities based on workload , so that the location / relocation would be easier and rational known as the workload indicators of staffing need ( wisn ) .Meeting the needs of of human resources in hospital was a the tone for hospital management .The management of the hospital have to are able to count needs human resources precisely on demand in each service unitMeeting the needs of excess of human resources in the hospital give a consequence labor costs high and gives rise to one of inefficiency of in financial management at the hospital .Lack of meeting the needs of human resources hospital give the effect of the workloads high to health workers and led the decline in of satisfaction with patient care , increase desire move work and diminishes the quality of patient safety. The number of human resources varied at every hospital in the city of medan.To achieve, vision and mission hospital skill and the ability of human resources needed to solve all problems is.From observation carried out in several hospitals in the city of medan, had shown an imperfection in planning the health workers and have not managed in a professional based on the workloads to the needs of human resources in every hospital. As a result , the available health numbers of workers have not been in accordance with a load of work and the real needs of in the field .The purpose of this research to analyze the needs of paramedics by counting discrepancy between the number of ideal paramedics ( skilled manpower including nurses and energy pharmacy ) by the fact that is said wisn difference and counting the workloads .The results of the study stated that the needs of labor is in accordance with the workloads is in some hospitals.